In vivo temporal penetration of mesenchymal stem cell-derived exosome eye drops across ocular tissue - Moon, Nian Lim; Qi, Hao Looi; Koh, Benson; Che’ Amat, Azlan; Muhammad, Numan; Khairuddin, Nurul Hayah (Universiti Putra Malaysia Press, 2023)
This study explores the potential application of extracellular vesicles (EVs) or exosomes derived from human mesenchymal stem cells (MSCs) in ophthalmology. Exosomes were isolated from MSCs’ culture supernatant, and applied as eye drops to rabbits’ eyes. Samples of aqueous (AH) and vitreous humour (VH) were collected at different time points for exosomes marker analysis. Our results showed that CD63 was detected in all AH and VH samples. Whereas, for CD9 and CD81, despite minimally expressed in control samples, showed varying expression in VH samples at different time points, indicating penetration and retention of exosomes in the eyes’ structure.